XBRL Topic Maps Challenge for Business Semantic Management - Andres, Frederic; Kannan, Rajkumar (Mapy pojęć XBRL zarządzające semantyką biznesową, 2010)
This paper presents an approach to analyze XBRL documents using semantic web technologies. XBRL is an XML-based standard widely used in the exchange and representation of accounting and business information between different organizations. The proposed system organizes XBRL documents under the topic maps data model (ISO/IEC1325) in relationship with an ontology-based PSI (Published Subject Identifiers) server describing financial information domain. The system enables the use of TMQL queries over the knowledge system that facilitates the analysis of the financial information. Currently the system is being developed as a collective intelligence business decision-making support.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 20-26
Keywords: topic maps; SaaS; knowledge modeling